Anastomotic Leak after Ileal Pouch–Anal Anastomosis - Guyton, Kristina; Kearney, David; Holubar, Stefan D. (Clinics in Colon and Rectal Surgery, 2021)
There are special considerations when treating anastomotic leak after restorative proctocolectomy and ileal pouch–anal anastomosis. The epidemiology, risk factors, anatomic considerations, diagnosis and management, as well as the short- and long-term consequences to the patient are unique to this patent population. Additionally, there are specific concerns such as “tip of the J” leaks, transanal management of anastomotic leak/presacral sinus, functional outcomes after leak, and considerations of redo pouch procedures.
Keywords: ulcerative colitis; Crohn's colitis; familial adenomatous polyposis; ileoanal pouch; AL; surgery; complications